"Core Values" Have Rights: Implementation of Organizational Culture and Work Culture - Mubais, Ahmad; Hikmah, Nur; Abror, A. Faiq (Jurnal Multidisiplin Sahombu, 2025)
The focus of this research is the implementation of organizational culture and work culture at the Central Bureau of Statistics (Badan Pusat Statistik/BPS) of Jepara Regency. Employing a qualitative descriptive method, the researcher conducted an in-depth exploration of the application of organizational culture and work culture within the institution. The data sources in this study are secondary data obtained from various relevant literature sources. Based on the findings, the researcher concludes that the implementation of organizational and work Culture at BPS Jepara Regency falls into the "moderately healthy" category, with a percentage score of 65.86%. This indicates that employees have demonstrated an exemplary implementation of organizational and work Culture in their daily work behavior.